THE ROLE OF SOCIAL ORGANISATIONS IN EMPOWERING MARGINALISED COMMUNITIES - Melyana R Pugu; Oggy Akmadani (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
Social organisations play an important role in helping disadvantaged communities. They work to improve the lives of people who are often overlooked or have difficulty getting help. The activities of social organisations include providing direct assistance, skills training, and trying to make changes in government policies. Despite facing many challenges, social organisations continue to strive to make a difference. They often work with governments and other groups to achieve their goals. The success of social organisations not only helps individuals, but can also improve society as a whole. The role of social organisations is invaluable in building a more just and prosperous society. They provide hope and support to those most in need, helping to create opportunities for people to better their own lives.